2012
DOI: 10.1080/08927014.2012.654779
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of byssogenesis on zebra and quagga mussels: the effects of water temperature, salinity and light–dark cycle

Abstract: The quagga mussel (Dreissena rostriformis bugensis) and zebra mussel (Dreissena polymorpha) are invasive freshwater bivalves in Europe and North America. The distribution range of both Dreissena species is still expanding and both species cause major biofouling and ecological effects, in particular when they invade new areas. In order to assess the effect of temperature, salinity and light on the initial byssogenesis of both species, 24 h re-attachment experiments in standing water were conducted. At a water t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…The higher byssal thread synthesis rate and attachment force of zebra mussels found by Peyer et al (2009) are a possible explanation for this difference in attachment behaviour. However, Grutters et al (2012) found no difference in byssal synthesis between quagga and zebra mussels at temperatures lower than 25°C. Despite the current dominance of the quagga mussel in the Great Lakes, relatively more zebra mussels were found on the hulls of resident boats than quagga mussels (Karatayev et al, 2013).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The higher byssal thread synthesis rate and attachment force of zebra mussels found by Peyer et al (2009) are a possible explanation for this difference in attachment behaviour. However, Grutters et al (2012) found no difference in byssal synthesis between quagga and zebra mussels at temperatures lower than 25°C. Despite the current dominance of the quagga mussel in the Great Lakes, relatively more zebra mussels were found on the hulls of resident boats than quagga mussels (Karatayev et al, 2013).…”
Section: Discussionmentioning
confidence: 67%
“…The zebra mussel Dreissena polymorpha (Pallas, 1771) and quagga mussel Dreissena rostriformis bugensis Andrusov 1897 have successfully invaded and continue to spread in both Western Europe and North America, making it important to assess their vectors for spread. These mussels are able to attach to several other organisms and various types of substrate by producing byssal threads (Grutters et al, 2012). Biofouling by dreissenids threatens native mollusc species and causes negative economic effects (Pimentel et al, 2005;Karatayev et al, 2007;Ward and Ricciardi, 2007;Oreska & Aldridge, 2011;Burlakova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…6). This difference might indicate a lower byssogenic activity, a process which is well known to be influenced by multiple environmental parameters [96], including the intensity of water currents and exposure to waves, factors which could not be controlled in the sites of sampling.…”
Section: Resultsmentioning
confidence: 99%
“…Dreissena bugensis spread in the same area during the midtwentieth century (Therriault et al 2005). This led to the co-occurrence of both species in their native (Zhulidov et al 2004) and introduced areas (Grutters et al 2012). During the last decades, there have been widespread observations of a shift going from the first introduced D. polymorpha to the recent invader D. bugensis as the dominant species (Matthews et al 2014;Marescaux et al 2015;Ginn et al 2018).…”
Section: Introductionmentioning
confidence: 99%